Analysis of communication between RFID tags and their reader using statistical simulation model. (19th September 2008) - Parikh, C.; Zeid, I.; Kamarthi, S.; Benneyan, J.
RFID collision occurs when two or more tags attempt to send a frame of data along the same communication channel at the same time. Collision typically results in false alarm. In this paper the authors simulate the communication flow between tags and their reader to investigate how acceptable reading time (defined as the reading time required to keep the rate of false alarms below 5%) is influenced by the size of tag population, data frame length, mean thinking time, and the statistical distribution of thinking time. The paper presents the results of the investigation and the effect of each parameter.